Tools and Resources to Combat Illegal Wildlife Trade - World Bank Group (World Bank, Washington, DC, 2018)
The Illegal Wildlife Trade (IWT) has reached an unprecedented scale, in part due to increasing demand from consumers. It is widely recognized that this criminality threatens peace, security, livelihoods, and biodiversity. The illegal trafficking in protected fauna and flora generates significant profits. IWT occurs globally and involves a multitude of species both iconic and lesser known. The response to IWT is multifaceted. It involves multiple national actors and agencies, numerous intergovernmental organizations (IGO) and national and international nongovernmental organizations (NGO), across borders and jurisdictions. This report provides an overview of the key types of tools and resources available to officials in the criminal justice system for combating IWT, and provides examples of prominent tools and resources, where appropriate. It describes both publicly-available and restricted tools.